A Feasibility Study of Microbialites as Paleomagnetic Recorders - (:unkn) unknown (My University, 2020)
Microbialites are carbonate organosedimentary deposits formed by benthic microbial communities that trap and bind detrital sediments, and/or inorganic and biologically influenced calcification. Any ferromagnetic particles incorporated into the microbialite structure have the potential to preserve variations in Earth’s magnetic field. A paleomagnetic record in microbialites would be useful for reconstructing the geomagnetic field because it may record at a high temporal resolution based on estimated growth rates, thus preserving relatively short-period variations of the Earth’s magnetic field. In addition, microbialites can be found in the geologic record going back ~3.5 Ga, hence potentially providing information on very ancient variations in the geomagnetic field. The purpose of this study is to evaluate whether microbialites are capable of reliably recording the Earth’s magnetic field by using paleomagnetic studies and rock magnetic methods on ancient and modern microbialites. This thesis is designed to answer the associated sub- questions: 1) Do microbialites carry a magnetization that is stable in time? What are the spatial variations in magnetization within the microbialite structure? (Chapter 3: Microbialite Magnetism and Stability); 2) Do microbialites accurately record Earth’s magnetic field direction? (Chapter 4: Paleomagnetic Directional Analysis); 3) What are the magnetic carriers in the microbialites? (Chapter 5: Magnetic Properties of Microbialites); and 5) What is the magnetization process or theorigin of the magnetization? (Chapter 6: Microbialite Magnetization Processes). To answer these questions, microbialites from four locations were collected: 1) Living and lithified hypersaline microbialites from the Great Salt Lake (GSL), Utah, U.S.A.; 2) living and lithified freshwater microbialites from Laguna Bacalar (LB), Quintana Roo, Mexico; 3) an ancient lacustrine environment microbialite from the Eocene Green River formation (GR), Wyoming, U.S.A; and 4) a marine, lower Cambrian Bayan Gol formation (BG) stromatolite, South Western Mongolia. Samples’ spatial and temporal variations in magnetic susceptibility (χ) and natural remnant magnetization (NRM) intensity were measured (Chapter 3) for assessing stability, reliability of the recorded magnetization, and to better understand magnetization processes. Microbialites were subjected to a stepwise alternating field (AF) or thermal demagnetization, to isolate a characteristic remanent magnetization (ChRM) which is compared with the expected field direction (Chapter 4). To identify the magnetic mineralogy (Chapter 5) seven tests were conducted: (1) S-ratio, (2) isothermal remanent (IRM) unmixing, (3) Lowrie-Fuller test, (4) 3D IRM technique, (5) Curie temperature, (6) hysteresis loops, and (7) first order reversal curve (FORC) experiments. To understand the microbialite magnetization processes, three more tests were conducted: (8) NRM intensity was compared to an anhysteretic remanent magnetization (ARM), (9) Anisotropy of Magnetic Susceptibility (AMS), (10) low-temperature test for biogenic magnetite. Results demonstrate that microbialites contain ferromagnetic materials that carry a stable magnetization. However, χ measurements show that magnetic mineralogy changes as living samples are removed from their environments (Chapter 3). With the exception of the GR microbialite, all microbialites record a direction close to the expected field directions (Chapter 4). Based on the tests (1) - (7), all microbialites show a predominant coercivity component around 30- 50 mT, which is interpreted to be magnetite. The two ancient microbialites additionally havesignificant contributions from higher coercivity components, including hematite, which do not contribute significantly to NRM (Chapter 5). The major magnetization processes are interpreted as a detrital remanent magnetization with the possible additional presence of biomagnetization based on the tests (8) and (9). Microbialites appear to have a high potential for paleomagnetic reconstruction. However, in order to use microbialites as paleomagnetic recorders, magnetization intensity should be more than 1.00E-07Am2/kg. For paleomagnetic reconstruction, samples should be collected from the middle of the structure, or the directional deviations should be averaged out in a layer. For an assessment of magnetic mineralogy from living microbialites, environmental and laboratory setting such as water current, humidity, temperature, and pH conditions should be considered.
Keywords: Microbialites; Paleomagnetism; Remanence acquisition; Stromatolites